Recent solubility and dissolution enhancement techniques for repaglinide a BCS class II drug: a review - Saba Albetawi; Amer Abdalhafez; Ala Abu-Zaid; Aseel Matrouk; Noor Alhourani (Pensoft Publishers, 2021)
Repaglinide is an oral blood-glucose-lowering drug used to manage type-2 diabetes mellitus by lowering post-prandial glucose by stimulating insulin secretion from pancreatic beta cells. According to the biopharmaceutical classification system, repaglinide falls under the class II category. For such drugs, limited solubility and poor dissolution rate are the major hurdles to overcome by formulation scientists, as they hinder drug absorption and lead to inadequate therapeutic effects. Therefore, this review aims to discuss in depth the various approaches investigated in the past five years to improve the solubility and dissolution of orally administered repaglinide: namely, solid dispersion, co-amorphous technology, cyclodextrin complexation, phospholipid complexes and polymeric micelles, nanocrystals, nanosuspensions and nanofibers.